IgG4-related spinal pachymeningitis. Issue 6 (June 2016) - Lu, Zhang; Tongxi, Liu; Jie, Luo; Yujuan, Jiao; Wei, Jiang; Xia, Liu; Yumin, Zheng; Xin, Lu
Abstract The aim of this study is to study the clinical, laboratory, imaging pathology, and prognosis features of IgG4-related spinal pachymeningitis. We worked with a 55-year-old man suffering from IgG4-related spinal pachymeningitis who had the most widespread lesion in his dura mater. We also review previous related studies and discuss the clinical characteristics of this rare disease. In total, eight IgG4-related spinal pachymeningitis patients have been reported in the literature since 2009. They were mostly male patients, 51.7 ± 11.9 years old on average. Cervical and thoracic vertebrae were the most common sites for lesions. The most prominent symptom was varying numbness and weakness of the limbs and/or body associated with spinal cord compression. There was one patient (1/5) with elevated serum IgG4 levels and three patients (3/3) with increased cerebrospinal fluid (CSF) IgG4 index. Positive histopathologic findings are the strongest basis for a diagnosis. All the patients with IgG4-related spinal pachymeningitis responded well to glucocorticoid therapy. IgG4-related spinal pachymeningitis is an orphan disease that mainly occurs in cervical and thoracic vertebrae. Older males are the most susceptible group. Serum IgG4 levels were consistently normal in these cases, so analysis of CSF for IgG4 production (IgG4 index) could become a useful tool. Pathological findings remain the gold standard for diagnosis. Most patients responded favorably to glucocorticoid treatment.